2023
DOI: 10.3389/fmicb.2022.1050699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of submerged macrophytes (Elodea nuttallii) on water quality and microbial communities of largemouth bass (Micropterus salmoides) ponds

Abstract: Traditional aquaculture ponds are one of the most vulnerable ecosystems; thus, ecological aquaculture is increasingly valued for its beneficial ecological properties and ecosystem services. However, little is known about ecological aquaculture of largemouth bass with submerged vegetation. Here, we designed three ecological ponds of cultured largemouth bass with submerged macrophytes (the EM group) and three ponds with traditional aquaculture (the M group) to reveal the response of water quality, and phytoplank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In this study, a-diversity and b-diversity analysis of the microbiota showed that compared to the control and SMA treatment group, CMA treatment group exhibited higher diversity among the microbial community, particularly of chao1 index at 32 d (17.58% higher than that of the control group), indicating the effectiveness of CMA treatment in improving species diversity of water microorganism and regulating the structure of water flora. There was a strong correlation between water quality and the species diversity of water microorganism, contributing to the stability of aquaculture ecosystem for M. salmoides (Nie et al, 2022). Simultaneously, LEFSe analysis demonstrated that the relative abundance of Bacteroides was higher in the control group at 32 d (p value < 0.05), indicating that compared to SMA and CMA treatment group, the aquatic environment of the control group has undergone severe eutrophication (Wagner and Loy, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…In this study, a-diversity and b-diversity analysis of the microbiota showed that compared to the control and SMA treatment group, CMA treatment group exhibited higher diversity among the microbial community, particularly of chao1 index at 32 d (17.58% higher than that of the control group), indicating the effectiveness of CMA treatment in improving species diversity of water microorganism and regulating the structure of water flora. There was a strong correlation between water quality and the species diversity of water microorganism, contributing to the stability of aquaculture ecosystem for M. salmoides (Nie et al, 2022). Simultaneously, LEFSe analysis demonstrated that the relative abundance of Bacteroides was higher in the control group at 32 d (p value < 0.05), indicating that compared to SMA and CMA treatment group, the aquatic environment of the control group has undergone severe eutrophication (Wagner and Loy, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…The data were analyzed on the free online platform of Majorbio I-Sanger Cloud Platform (cloud.majorbio.com (accessed on 20 November 2019)). The detailed analysis methods in this section were introduced in Nie et al [21].…”
Section: Dna Extraction and High Throughout Sequencingmentioning
confidence: 99%